LEMBAGA WALI NANGGROE ANTARA PERAN ADAT DAN POLITIK: SUATU ANALISIS TERHADAP QANUN ACEH NOMOR 10 TAHUN 2019 PERUBAHAN KEDUA ATAS QANUN ACEH NOMOR 8 TAHUN 2012 TENTANG LEMBAGA WALI NANGGROE - Januar, Eka (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2021)
The birth of Qanun number 17 of 2013 concerning the Aceh Truth and Reconciliation Commission is the result of a derivative of Law number 11 of 2006 concerning the Government of Aceh (UUPA), which is a derivative of the result of the Helsinki Peace Memorandum of Understanding (MoU) between the Republic of Indonesia (RI) and the Free Aceh Movement (GAM) on August 15, 2005 in Helsinki, Finland. This paper discusses the opportunities for the Acehnese Conflict Survivors/Victims Association as Social Capital in the existence of Qanun number 17 of 2013 to settle the fulfillment of the rights of victims of human rights violations that occurred in Aceh in the period 1976-2005. This type of research is a qualitative research. The process of collecting data using the method of observation of the object of research related to the one being studied, interviews starting from listening, arranging words, and summarizing the results of the interviews without losing the substance of the information conveyed by the informants. The data analysis technique in this study used descriptive techniques using data reduction. The results of this study indicate that from its journey, especially after the Aceh Peace, SPKP-HAM Aceh was present in various issues related to human rights violations during the Aceh conflict, especially after the Aceh peace. The birth of Qanun number 17 of 2013 was a part of the SPKP-HAM advocacy with other institutions as well as Acehnese students in 2010 during the occupation of the Aceh DPR building. Furthermore, various issues regarding the fulfillment of the rights of victims of human rights violations, this organization also criticizes government policies that do not take sides with victims of conflict.